Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Merger Pada PT. Bank Syariah Indonesia (Persero), Tbk - Karmila, Mila; Handoko, Pryo; Sonjaya, Trisna (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The purpose of this study is to find out whether there are differences in financial performance in the Capital Adequacy Ratio (CAR), Net Operating Margin (NOM), Return On Assets (ROA), and Return On Equity (ROE) between before and after the merger at PT Bank Syariah Indonesia for the 2019-2022 period. This type of research is quantitative with the research method used is descriptive comparative. The data used is secondary data in the form of the company's financial statements before and after the merger. The analytical tool used to answer the hypothesis is the non-parametric test, namely the Wilcoxon Signed Rank Test. The results of this study based on the ratio showed that there are significant differences in the ratio of PT BSI's Net Operating Margin (NOM), Return On Equity (ROE) and Return On Assets (ROA) between before and after the merger. Meanwhile, the Capital Adequacy Ratio (CAR) did not show a significant difference between before and after the merger